Associations between serum vitamin D and the risk of female reproductive tumors: A meta-analysis with trial sequential analysis. Issue 15 (April 2018) - Yan, Lina; Gu, Yun; Luan, Ting; Miao, Miao; Jiang, Lisha; Liu, Yu; Li, Ping; Zeng, Xin
Abstract: Background: Female reproductive tumors are common with high morbidity and mortality worldwide; however, the association between gynecological tumors and serum vitamin D is controversial. The aim of this meta-analysis was to evaluate the relationship between insufficiency of serum vitamin D and the occurrence of benign and malignant gynecological tumors. Methods: Studies from inception to June 2017 were searched in the electronic databases: National Library of Medicine (PubMed), Web of Science (Clerivate), and Cochrane Database of Systematic Reviews (Cochrane Library, CDSR) by 2 investigators independently. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using a random-effects model. STATA 12.0 Software and Trial Sequential Analysis (TSA) software were applied for data analyses. Results: Overall, 8 studies (including 2391 patients and 5798 patients with and without female reproductive tumors, respectively) were eligible for the present meta-analysis. In the subsequent meta-analysis, the occurrence of vitamin D deficiency in the case and control groups were 52.36% and 48.70%, respectively; women with female reproductive benign and malignant tumors were 55.57% and 50.59%, respectively. Although, no conclusive association was found between vitamin D deficiency and female reproductive tumors (OR, 1.05; 95% CI, 0.85–1.31); vitamin D deficiency may be a risk factor of malignant female reproductive neoplasm, as shown by the pooled OR (95% CI):1.17 (1.02–1.33). Furthermore, based on the OR values, association of vitamin D insufficiency with disease type, study location, number of patients, and methods for detecting CLA was observed. Similar results in the sensitivity analysis were observed. TSA showed that the cumulative Z -curve crossed the traditional boundary line, rather than crossing the trial sequential monitoring boundary. However, the cumulative information failed to reach the required information size. Conclusions: Currently, vitamin D deficiency appears to be a common issue in females, and there may be an urgent need to improve the level of vitamin D. Furthermore, vitamin D deficiency may be a non-negligible risk factor of malignant female reproductive neoplasm. Undoubtedly, more trials are required in the future according to TSA. Abstract : Supplemental Digital Content is available in the text